Destabilising social inclusion and recovery, and pursuing 'lines of flight' in the mental health sector. Issue 6 (11th June 2020) - Barlott, Tim; Shevellar, Lynda; Turpin, Merrill; Setchell, Jenny
Abstract: People who have been diagnosed with serious mental illness have a long history of confinement, social stigma and marginalisation that has constrained their participation in society. Drawing upon the work of Gilles Deleuze and Felix Guattari, we have used the concepts of: assemblages, major and minor and deterritorialisation to critically analyse two pervasive and 'taken‐for‐granted' assemblages in mental health: recovery ( including clinical recovery, social recovery and recovery‐oriented practice) and social inclusion . Our analysis explores how dominant and oppressive forces have been entangled with liberating and transformative forces throughout both of these assemblages – with dominant forces engaging in ongoing processes of capture and control, and transformative forces resisting and avoiding capture. In pursuit of social transformation for people categorised with serious mental illness, deterritorialisation is posited as a potential way forward. To have transformation in the lives of mental health service users, we present the possibility that ongoing, disruptive movements of deterritorialisation can unsettle majoritarian practices of capture and control – producing liberating lines of flight .